Fighting Words as Free Speech - Stephen W. Gard (Washington University Law Quarterly, 1980)
This Article first explicates the current status of the fighting words doctrine and the elements necessary for its proper invocation. Then it advocates abandonment of the doctrine and recognition of fighting words as expression deserving of First Amendment protection.
Keywords: Breach of the peace; Freedom of speech; United States